2009 IEEE International Conference on RFID 2009
DOI: 10.1109/rfid.2009.4911196
|View full text |Cite
|
Sign up to set email alerts
|

Power-optimized waveforms for improving the range and reliability of RFID systems

Abstract: A major limitation in passive radio frequency identification (RFID) is the read range from the reader to tag, which is limited by the power available to the radio frequency integrated circuit (RFIC). The power-optimized waveform (POW) is a new type of multiple-tone carrier and modulation scheme that is designed to improve the read range and power efficiency of charge pump-based passive RFICs. This paper presents the POW concept, an estimation of effects on existing class 1 generation 2 RFID systems, several ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
124
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(128 citation statements)
references
References 4 publications
(4 reference statements)
4
124
0
Order By: Relevance
“…Interestingly, the overall RF-to-DC conversion efficiency of the rectenna is not only a function of its design but also of its input waveform. However, the waveform design has received less attention [5]- [7]. In [5], [6], a multisine signal excitation is shown through analysis, simulations and measurements to enhance the DC power and RF-DC conversion efficiency over a single sinewave signal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the overall RF-to-DC conversion efficiency of the rectenna is not only a function of its design but also of its input waveform. However, the waveform design has received less attention [5]- [7]. In [5], [6], a multisine signal excitation is shown through analysis, simulations and measurements to enhance the DC power and RF-DC conversion efficiency over a single sinewave signal.…”
Section: Introductionmentioning
confidence: 99%
“…However, the waveform design has received less attention [5]- [7]. In [5], [6], a multisine signal excitation is shown through analysis, simulations and measurements to enhance the DC power and RF-DC conversion efficiency over a single sinewave signal. In [7], various input waveforms (OFDM, white noise, chaotic) are considered and experiments show that waveforms with high peak to average power ratio (PAPR) increase RF-to-DC conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown in the literature that signals with timevarying envelope and high peak-to-average power ratio (PAPR) may under certain conditions operate rectifier circuits in a more efficient manner, which leads to improved performance in terms of RF-DC conversion efficiency [12]- [19]. The underlying motive for this is that high PAPR signals take advantage of the nonlinear dynamics of rectifying devices and make them operate in a region of their (i-v) curve that lead to larger mixing products at the desired DC output.…”
Section: Signal Selection For Optimum Rectifier Performancementioning
confidence: 99%
“…Several works have shown that under certain operating conditions it is possible to obtain improvement in the efficiency if using multi-sine, chaotic or modulated signals [12]- [19]. In this paper several aspects and advances in these two topics will be presented.…”
Section: Introductionmentioning
confidence: 99%